Fluid intake in male and female runners during a 40-km field run in the heat - Millard-Stafford, M.; Sparling, P. B.; Rosskopf, L. B.; Snow, T. K.; DiCarlo, L. J.; Hinson, B. T. (Journal of Sports Sciences, 1995)
To compare physiological responses, hydration status and exercise performance in similarly trained men and women in a hot, humid environment, 12 highly trained runners were studied during a simulated 40-km race. A 7% carbohydrate-electrolyte (CE) beverage was consumed prior to exercise (400 ml) and every 5 km (approximately 250 ml) during the run. The run times of the males and females did not differ significantly (173.5 +/- 8.5 and 183.8 +/- 4.2 min, respectively); nor did the rate of fluid intake relative to body mass (10.3 +/- 0.7 and 10.7 +/- 0.8 ml kg-1 h-1, respectively) or percent body mass loss (4.0 +/- 0.1% and 3.9 +/- 0.1%, respectively). During the run, %VO2 max, heart rate, concentrations of blood lactate, serum total protein and plasma osmolality were also similar for both groups. However, some significant sex differences (P < 0.05) were observed: the females had lower plasma volume losses and higher serum potassium and sodium concentrations than the males during the run. Rectal temperatures were lower in the female runners compared with the males during the last 10 km of the run (0.7 degrees C) and recovery (1.1 degrees C). Findings from this 40-km field run in hot, humid conditions suggest that CE fluid replacement at a relatively similar dosage (approximately 10 ml kg-1 h-1) may have sex-specific physiological effects. These observations warrant further investigation to assess the need for sex-specific fluid replacement guidelines.